Light metal functionalized two-dimensional siligene for high capacity hydrogen storage: DFT study. (18th August 2021) - Sosa, Akari Narayama; Cid, Brandom Jhoseph; Miranda, Álvaro; Pérez, Luis Antonio; Salazar, Fernando; Trejo, Alejandro; Cruz-Irisson, Miguel
Abstract: In this work, the hydrogen storage capacities of two-dimensional siligene (2D-SiGe) functionalized with alkali metal (AM) and alkali-earth metal (AEM) atoms were studied using density functional theory calculations. One AM (Li, Na, K) or AEM (Be, Mg, Ca) atom was placed on the 2D-SiGe surface, and several H2 molecules were placed in the vicinity of the adatom. The results demonstrate that the most favorable siligene site for the adsorption of Li, Na, K and Be atoms is the hollow site, while for the Mg and Ca atoms is the down site. The AM atoms are the only ones with considerable binding energies on the SiGe nanosheets. Pristine 2D-SiGe slightly adsorbs one H2 molecule per hollow site and, therefore, it is not suitable for hydrogen storage. In some of the AM- and AEM-decorated 2D-SiGe, several hydrogen molecules can be physisorbed. In particular, the Na-, K- and Ca-functionalized 2D-SiGe can adsorb six hydrogen molecules, whereas Li and Mg atoms adsorbed three hydrogen molecules, and the Be adatom only adsorbed one hydrogen molecule. The complexes formed by hydrogen molecules adsorbed on the analyzed metal decorated 2D-SiGe are energetically stable, indicating that functionalized 2D-SiGe could be an efficient molecular hydrogen storage media. Graphical abstract: Image 1 Highlights: Li, Na and K atoms strongly bind to siligene while avoiding clustering. Na-, K- and Ca-functionalization could improve siligene hydrogen-storage capacity. Li-, Be- and Mg-functionalized SiGe sheets have poor hydrogen-storage capacities. H2 molecules are physisorbed on Li-, Na-, K- and Ca-functionalized siligene. AM- and AEM-functionalized SiGe sheets with adsorbed H2 are energetically stable.